2020
DOI: 10.1016/j.heliyon.2020.e03495
|View full text |Cite
|
Sign up to set email alerts
|

Altered redox status, DNA damage and modulation of L-tryptophan metabolism contribute to antimicrobial action of curcumin

Abstract: Identification and development of newer and better antimicrobials from natural products represent ongoing research efforts by many investigators. Curcumin is a polyphenol commonly found in the plant Curcuma longa (better known as turmeric). It has been reported to possess several bioactivities including antioxidant, anti-cancer, anti-inflammatory, anti-diabetic, anti-fibrotic, and antimicrobial properties. However, little is known about the antimicrobial mode of action of curcumin, thus undermining its prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Stock cultures of selected Gram-positive and negative bacterial isolates were generated as reported elsewhere [ 16 , 17 ]. The purity of the strains was determined by streaking on nutrient agar plates that were incubated at 37 °C for 24 h. Only plates that showed pure colonies were sub-cultured and used for further studies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stock cultures of selected Gram-positive and negative bacterial isolates were generated as reported elsewhere [ 16 , 17 ]. The purity of the strains was determined by streaking on nutrient agar plates that were incubated at 37 °C for 24 h. Only plates that showed pure colonies were sub-cultured and used for further studies.…”
Section: Methodsmentioning
confidence: 99%
“…The agar diffusion method, as previously described [ 16 , 17 ], was used. In this assay, nutrient agar was prepared into 100 mL capacity conical flask with 50 mL nutrient medium, as outlined by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al investigated the novel antibacterial mechanism of curcumin against E. coli and found that curcumin could induce a bacterial apoptosis‐like response by reactive oxygen species (ROS) production, membrane depolarization, and Ca 2+ influx [98]. Curcumin alone or in combination with ascorbic acid led to lipid peroxidation and DNA damage in S. aureus and E. coli , suggesting that oxidative stress and DNA damage might be partly responsible for the antibacterial mechanism of curcumin [99]. Moreover, a carbocyclic curcumin analogue 2d had potent antibacterial activity against B. subtilis and MRSA; 2d inhibited the proliferation of B. subtilis by targeting FtsZ, destroyed the Z‐ring formation in bacteria within 5 min, and enhanced the GTPase activity of FtsZ [100].…”
Section: Structure and Function Of Ftszmentioning
confidence: 99%